The Effect of Training, Career Development and Competence on the Performance of PDAM Tirta Kamuning Employees in Kuningan Regency - Wike Roharyani; Siti Maryam; Yodi Rudiantono; Sandi Nasrudin Wibowo (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This study aims to analyze the effect of training, career development and competencies jointly and partially on the performance of PDAM Tirta Kamuning employees in Kuningan Regency. This study used quantitative methods using questionnaires. The population in this study was 161 permanent employees of PDAM Tirta Kamuning, Kuningan Regency. The sampling technique with proportional stratified random sampling and the number of samples determined based on the Slovin formula obtained by 62 respondents. Data analysis uses classical assumptions, multiple linear regression, coefficient of determination and hypothesis tests (t-test and F-test). The results showed that: (1) training had a positive and significant effect on employee performance as evidenced by the calculated tstatistic > ttable, namely 2.107 > 1.671 and the sig value of 0.039 < 0.05, (2) career development had a negative and significant effect on employee performance indicated by the calculated tstatistic < ttable namely -2,070 < 1,671 and sig value 0.043 < 0.05, and (3) competence has a positive and significant effect on employee performance indicated by a calculated tstatistic > ttable which is 3.087 > 1.671 and a sig value of 0.003 < 0.05. Meanwhile, the results of simultaneous tests showed that training, career development and competence had a significant effect on the performance of PDAM Tirta Kamuning employees in Kuningan Regency, which was shown by the calculated Fstatistic > Ftable, namely 7.964 > 2.76 and a sig value of 0.000 < 0.05.